PEMBERDAYAAN KADER KESEHATAN DALAM DETEKSI PTM (PENYAKIT TIDAK MENULAR) MENUJU LANSIA SEHAT SEJAHTERA DI POSBINDU RW 15 KELURAHAN ARENJAYA KOTA BEKASI JAWA BARAT TAHUN 2023 - Safrudin, Safrudin; Andreas Hariandja, Andy Martahan; Setiawan, Heru; Rosidawati, Rosidawati (IFI cabang Kota Bekasi, 2024)
ABSTRACT Population projections for 2010 – 2035, Indonesia will enter the elderly period, where 10% of the population will be aged 60 years and over. Elderly people experience many declines and changes in physical and psychological function. As a result of this decrease in functional capacity, elderly people do not respond to various stimuli as effectively as younger people. Decreased capacity to respond to stimuli makes it difficult for elderly people to maintain body homeostasis, causing dysfunction of various organ systems and increasing susceptibility to disease. Homeostatic disorders that often occur are disorders in the regulation of blood uric acid and cholesterol levels. High levels of purine acid and cholesterol in the blood are a serious health problem because these two parameters are risk factors for various non-communicable diseases. Non-Communicable Diseases (NCDs) are one of the causes of death in the world. Indonesia is one of the countries that faces problems with both infectious diseases and non-communicable diseases (NCDs). This PTM usually appears without symptoms and does not show any particular clinical signs, so most people are not aware of the dangers of this non-communicable disease. If the public knows about early detection of this non-communicable disease, then efforts to prevent the occurrence of this disease will be carried out immediately. The aim of this community service is through training Posbindu cadres, providing knowledge about non-communicable diseases and carrying out routine blood pressure checks, blood sugar, uric acid and cholesterol checks to carry out early detection of non-communicable diseases. This community service uses counseling methods and is followed by providing consultations for elderly people who need them. Implementation of activities will be divided into 2 stages, namely the month (Jan - June) 2023 and the month (July - December) 2023. Indicators of the success of these community service activities are measured using pre and post tests for each extension material. Data on the health of elderly service participants will also be collected, especially data on blood uric acid and cholesterol levels. The output of the service is planned to be in the form of scientific articles and educational booklets/leaflets. Keywords: NCDs; blood sugar, uric acid, cholesterol.